An improved method to determine PM-bound nitro-PAHs in ambient air. (October 2016) - Tutino, Maria; Di Gilio, Alessia; Laricchiuta, Antonello; Assennato, Giorgio; de Gennaro, Gianluigi
Abstract: Nowadays, no a standard method for the determination of particulate bound nitro-PAHs (NPAHs) has been developed. Existing methods include complex sampling and extraction procedures. Moreover, their sensitivity does not allow to analyze daily PM10 samples, affecting the temporal resolution of NPAH concentrations. In this study an analytical method for the quantification of NPAHs on half 47 mm-filter samples of daily PM10 was developed and validated. NPAHs were recovered by microwave-assisted extraction, and analyzed by using a gas chromatography-triple quadrupole mass spectrometry in MRM mode. The analytical performance for 14 NPAHs (2-nitrofluorene, 9-nitroanthracene, 9-nitrophenantrene, 3-nitrophenantrene, 2-nitroanthracene, 3-nitrofluoranthene, 1-nitropyrene, 2, 7-dinitrofluorene, 7-nitrobenzo[a]anthracene, 6-nitrochrysene, 1, 3-dinitropyrene, 1, 8-dinitropyrene, 1, 6-dinitropyrene, 6-nitrobenza[ a ]pyrene) was investigated. Recovery extraction percentage exceeded 95% for all target compounds in the range between 0.25 and 10 ng/mL. The repeatability, expressed as Relative Standard Deviation percentage (RSD%) of five determinations, was less than 10% for target compounds except for 2, 7-dinitrofluorene, 1, 3- and 1, 8-dinitropyrene (RSD% < 15%). The limit of detection (LOD) ranged from 12 to 84 pg/mL for most of NPAHs, except for dinitro-pyrenes and nitro-benzo(a)anthracene for which the LOD reached 1.8 ng/mL. The method developed was applied to real samples in order to evaluate the levels of NPAHs in the urban and industrial area of Taranto (South of Italy). The analysis of PM10 samples collected at four industrial and one urban sites, highlighted that in proximity of critical emission source as the biggest European steel plant and under certain weather conditions, combustion processes were the main source of NPAHs in atmosphere. Graphical abstract: Highlights: Analytical method for analysis of fourteen particle-bound NPAHs was developed. PM10 microwave-assisted extraction and GC-QQQ-MS analysis were performed. High repeatability (RSD% < 10%) and sensitivity for NPAHs determination were obtained. NPAHs levels around the biggest European steel plant were determined. Primary and secondary NPAHs affect the area around the biggest steel plant in Europe.